Diesel soot and NOx abatement: K/La2O3 catalyst stability - Peralta, María Ariela (2010)
Soot particles and nitrogen oxides are the main pollutants emitted by a diesel engine. In this work, the activity and the stability of the KOH/La2O3 catalyst are studied. This catalyst is able to adsorb NOx, which is a good property for the catalyst in order to be used as a NOx trap. In addition, it is active for soot combustion as determined by temperature-programmed oxidation analyses. FTIR, XRD, CO2-TPD, Pulses of CO2, and BET techniques are used in order to characterize the catalysts. The catalytic surface composition depends upon the relative partial pressures of H2O, CO2, NO and O2. Despite the different surface compositions, the catalytic activity remains quite stable, under operation conditions similar to those of a real diesel exhaust. High temperature treatments, such as 800°C, and especially in the presence of water, leads to an irreversible catalyst deactivation due to potassium volatilization. The water condensed on the catalyst, could wash-out a fraction of the potassium from the outer surface, leading to a decrease in activity. However, when the catalyst is treated at 400°C, potassium diffuses from inside the pores to the external surface, thus recovering activity for soot combustion.